2023
DOI: 10.1108/md-05-2022-0641
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation, CEO power and firm performance: an upper echelons theory perspective

Abstract: PurposeAdopting insights from the upper echelons theory, this study aims to investigate the relationship between entrepreneurial orientation (EO) and firm performance under the contingent influence of chief executive officer (CEO) power.Design/methodology/approachData were collected from a sample of large publicly-traded Indian software firms using the Prowess Database of Center for Monitoring Indian Economy (CMIE). Panel data regression analysis was used to test the study's hypotheses.FindingsThe results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…Moreover, there is no consensus in the academic community on whether celebrity CEOs have an inhibitory or promotional effect on firm performance. Some scholars argue that celebrity CEOs can enhance company performance and bring about excess returns ( Nguyen, 2015 ; Bao et al, 2023 ), while others suggest that celebrity CEOs may engage in rent-seeking behavior or conceal negative information about the company, leading to a decline in firm performance ( Malmendier and Tate, 2009 ; Cho et al, 2016 ; Saiyed et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is no consensus in the academic community on whether celebrity CEOs have an inhibitory or promotional effect on firm performance. Some scholars argue that celebrity CEOs can enhance company performance and bring about excess returns ( Nguyen, 2015 ; Bao et al, 2023 ), while others suggest that celebrity CEOs may engage in rent-seeking behavior or conceal negative information about the company, leading to a decline in firm performance ( Malmendier and Tate, 2009 ; Cho et al, 2016 ; Saiyed et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To maintain their social status and personal benefits, celebrity CEOs may engage in self-interest or even unethical behavior to continuously improve firm performance or attract social attention, which can have negative implications for the firm. These negative impacts include rent-seeking behavior, hiding negative information about the firm, and ultimately leading to a decline in firm performance ( Malmendier and Tate, 2009 ; Cho et al, 2016 ; Saiyed et al, 2023 ). Other studies indicate that celebrity CEOs have only a short-term promotional effect on company performance and, in the long run, may cause negative market reactions ( Wade et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely referred theory about CEO power literature is agency theory. Based on this theory, studies have found that CEO power leads to lower firm value and performance (Bebchuk et al 2011;Veprauskaitė and Adams 2013;Duru et al 2016); needs increased monitoring by outside directors (Combs et al 2007), could lead to entrenchment (Finkelstein and D'Aveni 1994); lower leverage (Jiraporn et al 2012;Chintrakarn et al 2014); poor credit rating and higher bond yields (Liu and Jiraporn 2010); lower bank risk-taking (Pathan 2009); moderates the positive relation between board strength and firm strategy (Tuwey and Tarus 2016); lower dividend payout (Chintrakarn et al 2018); use less equitybased compensation that weakens board monitoring (Ryan and Wiggins;2004); lower CSR exposure and alleviates the positive effect of board capital on CSR exposure (Muttakin et al 2018); reduces the effect of ESG disclosure on market-based risk than accountingbased risk (Menla ; positively influences earnings management (Le et al 2022); lower R&D investment (Naaman and Sun 2022); lower entrepreneurial orientation (Saiyed et al 2023); lower idiosyncratic volatility (Tan and Liu 2016); positively related Director reputation theory: directors pursue to create and uphold their reputation, thereby improving their human capital to enhance their chances of getting appointments in other boards Fama (1980); Fama and Jensen (1983) Zajac and Westphal (1996a, b); Zajac and Westphal (1996b) to CSR (Pucheta-Martínez and Gallego-Álvarez 2021); lower corporate sexual orientation policies (Brodmann et al 2021).…”
Section: Theories That Have Received Mixed Supportmentioning
confidence: 99%
“…They found that CEO emotional stability and agreeableness are positively related to cost efficiency and profitability, whilst CEO conscientiousness is negatively related to them. Based on the upper echelons theory, Saiyed et al (2023) explore the effects of entrepreneurial orientation and CEO power on firm performance. Their results suggest that CEO power plays a negative moderating role on the inverted U-shaped relationship between entrepreneurial orientation and financial performance, indicating that powerful CEOs are likely to harm entrepreneurial enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…They found that CEO emotional stability and agreeableness are positively related to cost efficiency and profitability, whilst CEO conscientiousness is negatively related to them. Based on the upper echelons theory, Saiyed et al. (2023) explore the effects of entrepreneurial orientation and CEO power on firm performance.…”
Section: Introductionmentioning
confidence: 99%